Tailoring durable MnOx-based electrodes for high-performance electrocatalytic function for next-generation electrocatalysis applications - Hashem Tayeba; Roya Kiani-Anbouhi; Neda Royaei (Materials for Renewable and Sustainable Energy)
Abstract This study introduces a high-performance electrode coated with MnOx compounds to enhance the HER reaction. The active and precipitated MnOx species facilitate interconnected electron transport throughout the Ti electrodes. The tailored MnOx electrodes exhibited a significant reduction in Rct (69.7%), superior Cdl (31.6%), and a notably lower Nyquist ring compared to traditional Ti electrodes, confirming their excellent electrocatalytic performance in Cl− and NaCl production. Additionally, LSV and PDP analysis demonstrated that the MnOx electrodes achieved a 53.9% decrease in Tafel slopes (from 139 mV/decade to 64 mV/decade), lower activity potentials, and robust corrosion resistance (99.4%), indicating faster kinetics and higher efficiency. High-resolution FESEM and contact angle images revealed that the MnOx electrodes possess uniform porous networks and semi-super hydrophilic function, optimizing H2 release and expanding the interfacial area for electron transfer. Finally, the Ti electrodes with advanced MnOx coatings can serve as reliable, cost-effective, and efficient candidates for use as regenerating electrodes in electrocatalytic industries. Moreover, the novel MnOx/rGO composites are versatile materials used as catalysts in chemical reactions, effective electrodes in energy storage devices, sensitive gas sensors, and for water treatment to remove contaminants.